The Development of Chemireligiousa Teaching Material Integrated with Character Education in Chemistry Learning of Hydrocarbon Material in SMK - Ningrum, Lis Setiyo; Supardi, Kasmadi Imam; Jumaeri, Jumaeri; Haryani, Sri (Postgraduate, Universitas Negeri Semarang, Indonesia, 2018)
Character education is very important in education. The integration of teaching materials with character education is one way that can be done. This study aims to obtain chemireligiousa teaching materials integrated character education on SMK hydrocarbon material that is valid, effective and students' response to teaching materials. The development model was a 4-D development model by Thiagarajan, Semmel & Semmel consisting of four stages: (1) Define (definition), (2) Design (Design), (3) Develop and (4) Disseminate (Spreading). The results of the preliminary study indicate that has not been found chemireligiousa teaching materials integrated education of hydrocarbon material character for students of SMK and chemireligiousa teaching materials integrated character education was indispensable in learning in vocational schools. Teaching material development results obtained a validity score of 0,94, so the criterion of teaching material was valid. The effectiveness of teaching materials was reviewed from the students' clarity completeness of 89% and the N-Gain test of 0.76 (height). Students respond very well to the use of integrated chemireligious materials teaching character education, with an overall average of 3.42. Based on the acquisition of data research results can be stated that the developed teaching materials valid, effective and get a good response from students’s.